Attending Physician Variability: A Model of Four Supervisory Styles. (November 2015) - Goldszmidt, Mark; Faden, Lisa; Dornan, Tim; van Merriënboer, Jeroen; Bordage, Georges; Lingard, Lorelei
Abstract : Purpose: There is wide variability in how attending physician roles on teaching teams, including patient care and trainee learning, are enacted. This study sought to better understand variability by considering how different attendings configured and rationalized direct patient care, trainee oversight, and teaching activities. Method: Constructivist grounded theory guided iterative data collection and analyses. Data were interviews with 24 attending physicians from two academic centers in Ontario, Canada, in 2012. During interviews, participants heard a hypothetical presentation and reflected on it as though it were presented to their team during a typical admission case review. Results: Four supervisory styles were identified: direct care, empowerment, mixed practice, and minimalist. Driven by concerns for patient safety, direct care involves delegating minimal patient care responsibility to trainees. Focused on supporting trainees' progressive independence, empowerment uses teaching and oversight strategies to ensure quality of care. In mixed practice, patient care is privileged over teaching and is adjusted on the basis of trainee competence and contextual features such as patient volume. Minimalist style involves a high degree of trust in senior residents, delegating most patient care, and teaching to them. Attendings rarely discussed their styles with the team. Conclusions: The model adds to the literature on variability in supervisory practice, showing that the four styles reflect different ways of responding to tensions in the role and context. This model could be refined through observational research exploring the impact of context on style development and enactment. Making supervisory styles explicit could support improvement of team competence.